1994
DOI: 10.1002/jlac.15619940509
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroism and absolute configuration of Aza‐ and Thiaflavanones

Abstract: The correlation between the absolute configuration and CD of aza-and thiaflavanone (1, 2) is discussed: the 2R configuration for the laevorotatory enantiomers has been established by a comparison of their CD data with those of ( S ) -( -) -3 . For the Cotton effect within the n + I[* band of 1 and 2 the same helicity rule is valid as for the homochirally analogous flavanones (3). Starting from (S)-( -)-flavanone (3) and cholesterol Recently, the optical resolution of azaflavanone[l3I (1) and thiaflavanone[I41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
2
15
1
Order By: Relevance
“…The S -configuration of C-2 was determined by a positive Cotton effect observed at 312 nm and a negative one at 286 nm in the circular dichroism (CD) spectrum of 43 . 22 Based on these observations, 43 was established as (2 S )-3′,5,8-trihydroxy-4′-methoxy-6,7-methylenedioxy-2′-prenylflavanone, and named antiarone L.…”
Section: Resultsmentioning
confidence: 99%
“…The S -configuration of C-2 was determined by a positive Cotton effect observed at 312 nm and a negative one at 286 nm in the circular dichroism (CD) spectrum of 43 . 22 Based on these observations, 43 was established as (2 S )-3′,5,8-trihydroxy-4′-methoxy-6,7-methylenedioxy-2′-prenylflavanone, and named antiarone L.…”
Section: Resultsmentioning
confidence: 99%
“…According to our rule this should lead to a negative 1 L b band CD, which was found experimentally. 37 The chiroptical properties of model compounds (−)-10, (+)-14, and (−)-18 showed that P/M helicity of the Oheterocyclic ring in the chromane chromophore is reflected by a negative/positive Cotton-effect within the 1 L b band transition of the benzene ring when the Oheterocyclic ring adopts a half-chair conformation and there is no substituent on the fused aromatic ring. This rule can be safely used for 2,3-substituted chromane derivatives and it is also valid for the (2R;4R)-4-hydroxyflavan, 20, whose heterocyclic ring has half-chair conformation and its helicity is governed by the equatorial orientation of the phenyl group.…”
Section: 3-dihydrobenzo[b]furan and Chromanementioning
confidence: 99%
“…35,36 For the preparation of 10, 5 was treated with 2-(benzyloxy)-benzaldehyde to obtain the 2-arylidene ketone 6 in 60% yield (Scheme 1). 37 Next, the bulky 2-(benzyloxy)-benzyl group at C-2 of the cholestane skeleton was fixed in 2␣ configuration, namely, in the thermodynamically more stable equatorial position (6→7) in four steps. A mesyloxy group, a good leaving group, was introduced into C-3 in a stereocontrolled manner (7→8, 7→9) to obtain the suitable precursors for the S N 2-type ring closure.…”
Section: Chromane (4h-benzopyrane) Chromophorementioning
confidence: 99%
See 1 more Smart Citation
“…The absolute configuration of C-2 was determined to be S configuration by a negative cotton effect at 289 nm and a positive cotton effect observed at 331 nm in the circular dichroism (CD) spectrum of 2(Fig. 5)(Antus et al, 1994) (Shi et al, 2014). Thus, compound 2 was established as (2S)-4,5,7-trihydroxy-3 0 -methoxy-2 0 -prenylflavanone named antiarone M.Compound 3 was obtained as colorless oil.…”
mentioning
confidence: 99%